2022
DOI: 10.3389/fnut.2022.979651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 30 days of ketogenic Mediterranean diet with phytoextracts on athletes' gut microbiome composition

Abstract: BackgroundRecent research suggest that gut microbiome may play a fundamental role in athlete's health and performance. Interestingly, nutrition can affect athletic performance by influencing the gut microbiome composition. Among different dietary patterns, ketogenic diet represents an efficient nutritional approach to get adequate body composition in athletes, however, some concerns have been raised about its potential detrimental effect on gut microbiome. To the best of our knowledge, only one study investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…On the other hand, the effect of lower carbohydrate intake on gut microbial composition is a point of discussion [65,66]. It is important to consider that low carbohydrate diets with more balanced compositions may not alter gut microbial composition [67,68]. Therefore, it is crucial to emphasize that studies that evaluate the effect of dietary patterns on physical performance via the gut microbiota are not only necessary but also a potential area for future research.…”
Section: Strategies For Manipulating the Microbiome In Athletesmentioning
confidence: 99%
“…On the other hand, the effect of lower carbohydrate intake on gut microbial composition is a point of discussion [65,66]. It is important to consider that low carbohydrate diets with more balanced compositions may not alter gut microbial composition [67,68]. Therefore, it is crucial to emphasize that studies that evaluate the effect of dietary patterns on physical performance via the gut microbiota are not only necessary but also a potential area for future research.…”
Section: Strategies For Manipulating the Microbiome In Athletesmentioning
confidence: 99%
“…has been positively associated with cholesterol and LDL concentrations in hyperlipidemic rats. These findings suggest that adhering to a KD exerts selective pressure on the gut microbiota, which may have many consequences Mancin et al [27] conducted a linear discriminant analysis in the post-intervention period identified several genera that differentiated the two groups -western diet (WD) and ketogenic diet (KD) group. Bifidobacterium, Butyricicoccus, and Acidaminococcus were more abundant in the WD group, while Clostridia UCG-014, Butyricimonas, Odoribacterter, and Ruminococcus were more abundant in the KDP group.…”
Section: Stool Microbiotamentioning
confidence: 99%
“…Consequently, there is growing interest in investigating whether the gut microbiota acts as a mediator for various diseases such as obesity, diabetes, cardiovascular diseases, and non-alcoholic fatty liver disease (NAFLD) [ 7 ]. Furthermore, recent attention has focused on exploring the potential role of the gut microbiota as a mediator between dietary patterns, especially for specific micronutrients such as dietary fiber and anthocyanins (ACNs) that are abundant in dietary patterns, and sports performance in athletes [ 8 , 9 , 10 ]. However, most studies have primarily evaluated the effects of supplements, like probiotics, on athletic performance rather than deeply investigating the relationship between dietary patterns and sports performance through their impact on the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%